Efektivitas Kombinasi Hydroterapi Rendam Kaki Air Hangat dengan Campuran Garam dan Berdzikir terhadap Tekanan Darah pada Pasien Hipertensi di Wilayah Kerja Puskesmas Karangtengah Demak - Jihan Diyanah Iftinan; Apriliani Yulianti Wuriningsih; Sri Wahyuni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension is an abnormal increase in blood pressure in the arteries that persists over a period of time. Hypertension is defined as an increase in systolic blood pressure of at least 140 mmHg or diastolic blood pressure of at least 90 mmHg. Symptoms experienced by people with hypertension include dizziness, irritability, ringing in the ears, difficulty sleeping, shortness of breath, heaviness in the neck, fatigue, and blurred vision. The purpose of this study was to determine the effect of warm foot baths with salt and recitation of prayers on the blood pressure of patients with hypertension. The method used is quantitative, with a pre-experimental research design using a one-group pre-test-post-test design. Hydrotherapy is performed by soaking the feet in warm water mixed with salt and reciting prayers using 3 liters of warm water at a temperature of 38-40ºC mixed with 15 grams or 3 teaspoons of salt for 15-20 minutes. In addition to warm water foot soaking therapy, it can also be combined with incorporating elements of faith, one form of which is recitation. Sampling was conducted using non-probability sampling techniques. For the sample size in this study, the researcher used the Slovin sample size formula, which is used to calculate the minimum sample size in a finite population with a total sampling approach and 16 respondents. Conclusion: Warm foot bath therapy with salt mixture and recitation has an effect on blood pressure changes in hypertensive patients.